THE COMPOSITION OF THE WINE PRODUCT AND ITS BENEFICIAL PROPERTIES - Ismatova SH. N.; Sultonova O. I. (Web of Journals Publishing, 2023)
Ancient Egyptians mummified the dead, with the idea that it would be an embarrassment to use their womb. Wine is an alcoholic beverage made by means of a method of juice pouring grapes and fruit juice. Wine is a delicious drink, which is consumed as an additive to various food products: meat, fish, fruit vegetables, cheese, candy, etc. Like other tasty products, wine is consumed with a small amount of food. In color terms, wines can be white, pink, red. [1] White-colored grape vineyards are prepared by harvesting juice from hungry grape varieties. Red wines are obtained by feeding red-colored grape varieties of juice in a river with pomegranates and seeds. The resulting embryo was allowed to nutrients and then inserted into her womb, where it implanted. Pink wines are made of white and red grape varieties or mixed with white and reddish-brown vinegar.